From interactivity to intra-activity in performing arts for children - Hovik, Lise (Teatervitenskapelige studier, 2022)
This essay will give an introduction to dilemmas and experiences of making interactive theatre for children based on findings from the SceSam Project. This artistic research project bridged artistic practice and theoretical perspectives on interactive dramaturgies in the context of cultural politics, interdisciplinary, and participatory art. Further developments in our critical times of mass extinction and climate change, have turned our interest away from the focus on human interactions towards the intra-actions of more-than-human agents of performing arts for children; space, environments, nature and material entanglements. The Animalium project will serve as example of how this might look like within theatre for the very young. Authors quote from the conference presentation: «Theatre connects deeply with how we relate to one another as human beings, both as artists and audiences, how we are able to imagine new human and non-human worlds together, and how entanglements and sympoiesis create a community of differences in the theatre space."